Adenosine Deaminase Gene Polymorphism and Baseline Serum Level of Adenosine Deaminase as a Biomarker of Response to Methotrexate in Rheumatoid Arthritis. Issue 8 (12th December 2021) - Gangadharan, Harikrishnan; Singh, Ankita; Majumder, Sanjukta; Aggarwal, Amita
Abstract : Background: Methotrexate (MTX) is the first-line therapy for rheumatoid arthritis (RA), but nearly 30% of RA patients do not respond to it. Methotrexate acts by enhancing the level of adenosine, which gets converted to inosine by the enzyme adenosine deaminase (ADA). We studied whether ADA gene polymorphism and serum levels of total ADA are associated with responsiveness to MTX. Methods: Two hundred seven disease-modifying antirheumatic drug–naive active RA patients (DAS28-ESR [Disease Activity Score–28 for rheumatoid arthritis with erythrocyte sedimentation rate] ≥3.2) satisfying the European League Against Rheumatism (EULAR)/American College of Rheumatology 2010 criteria were enrolled. Genotyping was done in all patients, and in a subset (n = 59), blood was collected at baseline and at 2 months of MTX treatment for serum total ADA estimation by ELISA. Response at 4 months was assessed by EULAR criteria, and patients were classified as responders or nonresponders. The correlation of baseline clinical parameters, ADA gene polymorphism, and serum total ADA levels with EULAR response was sought. Results: After 4 months of MTX monotherapy, 172 patients (83.1%) were classified as responders and 35 (16.9%) as nonresponders. Except DAS28-ESR (6.1 [5.43–6.84] in responders vs 5.6 [4.77–6.21] in nonresponders, p = 0.02), other baseline parameters (age, disease duration, ESR, and C-reactive protein level) were similar between responders and nonresponders. Single nucleotide polymorphisms in ADA gene, baseline serum ADA levels (10.52 ± 5.37 ng/mL in responders vs 12.28 ± 5.14 ng/mL in nonresponders), or change in ADA levels after 2 months of MTX therapy did not show any association with MTX response ( p = 0.73, p = 0.34, p = 0.55, respectively). Adenosine deaminase genotype did not affect the blood ADA level. Conclusions: No association was seen between ADA single nucleotide polymorphism rs244076 as well as serum ADA level and response to MTX therapy.